CONSTRUCTIVE DIALECTIC OF FOCUS GROUP DISCUSSION MODEL INTEGRATED WITH CRITICAL THINGKING IN AFFIRMATION LITERACY SKILL - Baharun, Hasan; Muali, Chusnul (QUALITY, 2018)
This paper presents the effectiveness of focus group Discussion and critical thinking model on literacy skills of educational supervisor in Ministry of Religious Affairs, Probolinggo, East Java, Indonesia. This study adopts a quantitative research approach and uses a a quasi-experimental quasi-experimental study with a randomized pretest-post-test with control group design. The study shows that there are differences of literacy ability in education supervisor in Ministry of Religious Affairs, Probolinggo between focus group discussion (FGD) with critical thinking literacy ability. The focus group discussion approach is more effective in improving literacy skill. The scientific work shown with the average post test score is higher than the treatment-treated class of critical thinking.